Pela Gandong for Social Reconciliation and Peacebuilding in Ambon - Tati Hartimah; Setyadi Sulaiman; Nina Farlina (Buletin Al-Turas, 2021)
This study aimed to explore the effectiveness of Pela Gandong in the process of social reconciliation and peacebuilding in Ambon. Using a sociocultural approach, this qualitative research attempted to examine the theory of social reconciliation in the peace-building process between two conflicting groups. The data that had been collected in the form of interviews, FGDs, and documentation sources related to pela gandong were qualitatively analyzed. The results of the research showed that structural segregation becomes a barrier to the process of social reconciliation because some communities and local elites still maintained inter-group beliefs about the existence of a common enemy due to past conflicts. Pela gandong played a role in strengthening social reconciliation amid actor antagonisms that were difficult to subside, factions among local elites that were still strong, and people who were still trapped in past traumas. Based on the spirit of pela gandong, the government and civil society, including educational institutions in Ambon, presented a peaceful atmosphere with various initiatives, starting from the formation of multi-ethnic villages, providing facilities and infrastructure for harmony, strengthening the curriculum for local wisdom "Pela Gandong" and “Pendidikan Orang Basudara” (POB), to strengthening interfaith mediation institutions in Maluku: Baku Bae, Maluku Interfaith Institution, and Maluku Interfaith Institution for Humanitarian Action. All of them were an effort to create a peaceful Ambon, make Maluku a laboratory for peace, a learning medium for other regions in Indonesia.